Effect of Citric Acid, Phytase and Calcium in Diets of Laying Hens on Productive Performance, Digestibility and Mineral Excretion - Vargas-Rodriguez , L.M.; Herrera, J.G.; Morales, E.J.; Arcos-Garcia, J.L.; Lopez-Pozos, R.; Ruelas, G. (International Journal of Poultry Science, 2015)
The objective of this experiment was to evaluate the effect of citric acid (CA), phytase and calcium in diets of laying hens on the productive performances and digestibility and excretion of phosphorus (P), calcium and nitrogen (N). An experiment was designed using 24 week old laying hens, which were fed a diet with a base of sorghum and soybean meal containing 2,700 kcal ME/kg, 15% crude protein, 3.25% calcium and 0.25% available phosphorus. The following were also added to the diets of hens depending on the treatment groups: 0.0, 0.6 and 1.2% citric acid, 0.0 and 300 units of phytase/kg of diet (FTU) and 3.00 and 3.25% calcium. The phytase was added as an ingredient into to diets, contributed to 0.1% of phosphorus and 0.3% of calcium levels. The experiment involved 12 treatments in a 3 × 2 × 2 factorial design. The treatment 0.6% citric acid, 300 FTU and 3% calcium increased the digestibility of phosphorus, resulting in its decreased excretion (p